Severity of Alcohol Dependence and Correlation with Age of Onset of Drinking In Rural Adult Males, Karnataka - Kusum Shrirang Mane; Sunil S Kadam (Medsci Publications, 2020)
Background: Alcoholism is one of the most challenging public health problem in most of the countries including India. In India it has shown a prevalence of 15-60 % for alcoholism. The study was conducted to determine the severity of alcohol dependence and also to determine the relationship between severity of alcohol dependence and age of onset of drinking. Materials and Method: The study was conducted among above 18 year ols males from rural field practice area attached to SSIMS & RC, Davangere. Systematic random sampling was used to select the houses. Participants were interviewed for socio-demographic and alcohol related information with the use of pre-tested questionnaire. Written consent was taken before starting the study. AUDIT and SADQ was used. Results: Total 265 participants were included in this study. 77% participants started drinking at the age of 18-20years. 57% participants showed the mild physical dependence. Severity of alcohol dependence is shown in those who have started drinking in early age. Conclusion: Majority of participants were young to start drinking alcohol and early initiation of alcohol showed the mild physical dependence among them.